2018
DOI: 10.1007/s40858-018-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Rice defense responses to Bipolaris oryzae mediated by a strobilurin fungicide

Abstract: Strobilurins, also known as quinone outside inhibitors (QoIs), are one of the most important fungicide groups for controlling plant diseases. In addition, they can prime plants for enhanced defense against pathogen attack. Here, detailed biochemical and microscopic analyses were performed to investigate whether azoxystrobin (Az) could enhance defense responses to Bipolaris oryzae, the cause of brown spot of rice. Fungal infection increased the activity of all defense enzymes regardless of fungicide treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…Their DNA sequences were uploaded to the GenBank database with accession 1; Figure 1). Bipolaris oryzae has been reported as a causal agent of brown spot disease in rice plants (Debona et al, 2018), which further supports this finding. As far as we are aware, this would be the first record of B. oryzae in Brunei Darussalam.…”
Section: Identification Of Fungi That Cause Rice Diseases In Brunei D...supporting
confidence: 76%
“…Their DNA sequences were uploaded to the GenBank database with accession 1; Figure 1). Bipolaris oryzae has been reported as a causal agent of brown spot disease in rice plants (Debona et al, 2018), which further supports this finding. As far as we are aware, this would be the first record of B. oryzae in Brunei Darussalam.…”
Section: Identification Of Fungi That Cause Rice Diseases In Brunei D...supporting
confidence: 76%
“…46 Therefore, PAL activity can be used as a physiological index of plant immunity. 47 Our results showed that pyraclostrobin increased the PAL activity, which enhanced the plant defense against soybean diseases. A similar effect occurred in rice plants, in which azoxystrobin (a strobilurin fungicide) significantly enhanced the PAL activity.…”
Section: Discussionsupporting
confidence: 49%
“…PAL is also the key synthesis enzyme for lignin, which can increase the thickness of the cell wall, the degree of woody tissue, and form a mechanical barrier against pathogen invasion . Therefore, PAL activity can be used as a physiological index of plant immunity . Our results showed that pyraclostrobin increased the PAL activity, which enhanced the plant defense against soybean diseases.…”
Section: Discussionmentioning
confidence: 62%
“…species but not in A. versicolor which was unchanged (Table 1). The effect of strobilurins against fungi is well documented, they appear able to enhance rice plant defenses against pathogen attacks [19,24], shown also in wheat against mycotoxigenic Fusarium species like F. graminearum [20]. The incidence of A. versicolor was too low to obtain a significant reduction in treatment with azoxystrobin, although a reduction of 5% was observed.…”
Section: Resultsmentioning
confidence: 99%
“…There are few fungicides allowed by Italian Regulations for rice; of these, azoxystrobin is an active ingredient belonging to the strobilurin chemical group and it is one of the most used on Italian rice because of its demonstrated efficacy on several crops and its major role in reducing Pyricularia grisea [18] and Bipolaris oryzae infections in rice [19] and Fusarium Head Blight (FHB) in wheat [20]. However, its possible effect on mycotoxins is still uncertain since in some studies the use of azoxystrobin in wheat could result in an increase in DON content up to 42% [21,22]; for this reason, this possible effect needs to be evaluated also in rice in order to assist farmers in their selection of fungicides.…”
Section: Introductionmentioning
confidence: 99%